Exploration of the Role of Women in the Novel Baitun Nakhil by Tarek Eltayeb: A Study of Ecofeminism - Humaira, Durrotun; Basid, Abdul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Women have a close relationship with nature, especially in traditional environments, so patriarchy and environmental damage are related from the perspective of ecofeminism. This research was conducted to understand and criticize feminine principles and characters that can protect the environment and nature. This research is descriptive qualitative. Primary data is obtained from narratives and dialogues contained in the novel, while secondary data comes from various books and journal articles related to the theme of discussion. Data were collected using reading and note-taking techniques and then analyzed using the Miles and Huberman method: data reduction, data pr esentation, and conclusion drawing. From this study, it can be concluded that the ecofeminism activities contained in the novel Baitun Nakhil are (1) colonialism and patriarchy in the narrative that describes the exploitation and domination of marginalized people and nature, such as the attack of armed groups on villagers and authoritarian family heads; (2) women's role in the sustainability of nature is in the form of environmental education and women's ability to maintain and provide the necessities of life; (3) social and environmental justice that can be assessed by the negative impact of deviant and dominating hierarchies such as the urbanization that occurred in the city of Al-Shams which resulted in the extinction of animal and plant habitats and ecosystems. Thus, the novel Baitun Nakhil by Tarek Eltayeb indirectly voices the message of ecofeminism in the form of narratives and dialogues that show that loving, caring, and sensitive attitudes are the initial capital to be able to care for nature and the environment.